Two new genera (Paraeperopeus and Dentimelita) and four new deep-sea amphipod crustacean species of little-known genera (Neohela, Pardaliscella, Pardaliscoides and Tosilus) from the Perdido Fold Belt, Gulf of Mexico. (22nd December 2021) - Paz-Ríos, Carlos E.; Pech, Daniel
Abstract: Two new genera and six new species of benthic amphipods from the soft sediments of the Perdido Fold Belt region, western Gulf of Mexico, are described. Morphological comparisons of the new species with description of their congeners resulted in the determination of one new genus and one new species of the family Melitidae as Dentimelita lecroyae gen. nov., sp. nov., one new genus and four new species of the family Pardaliscidae as Pardaliscella perdido sp. nov., Paraeperopeus longirostris gen. nov., sp. nov., Pardaliscoides ecosur sp. nov. and Tosilus cigomensis sp. nov., and one new species of the family Unciolidae as Neohela winfieldi sp. nov. The occurrence of the newly described amphipods in the Perdido Fold Belt region represented new geographic range extensions for the genera, including new records of Neohela in the Gulf of Mexico, Pardaliscella and Pardaliscoides in the western Atlantic and Tosilus in the Atlantic.